Bioprinted Living Coral Microenvironments Mimicking Coral‐Algal Symbiosis. (6th June 2022) - Wangpraseurt, Daniel; Sun, Yazhi; You, Shangting; Chua, Sing‐Teng; Noel, Samantha K.; Willard, Helena F.; Berry, David B.; Clifford, Alexander M.; Plummer, Sydney; Xiang, Yi; Hwang, Henry H.; Kaandorp, Jaap; et al.
Abstract: The coral‐algal symbiosis is the biological engine that drives one of the most spectacular structures on Earth: the coral reef. Here, living coral microhabitats are engineered using 3D bioprinting, as biomimetic model system of the coral‐algal symbiosis. Various bioinks for the encapsulation of coral photosymbiotic microalgae ( Breviolum psygmophilum ) are developed and coral mass transfer phenomena are mimicked by 3D bioprinting coral tissue and skeleton microscale features. At the tissue–seawater interface, the biomimetic coral polyp and connective tissue structures successfully replicate the natural build‐up of the O2 diffusive boundary layer. Inside the bioprinted construct, coral‐like microscale gastric cavities are engineered using a multi‐material bioprinting process. Underneath the tissue, the constructs mimic the porous architecture of the coral aragonite skeleton at the micrometer scale, which can be manipulated to assess the effects of skeletal architecture on stress‐related hydrogen peroxide (H2 O2 ) production. The bioprinted living coral microhabitats replicate the diffusion‐related phenomena that underlie the functioning and breakdown of the coral‐algal symbiosis and can be exploited for the additive manufacturing of synthetic designer corals. Abstract : Biomimetic living coral microhabitats are manufactured using 3D bioprinting. The biomimetic corals use a symbiont bioink and mimic mass transfer phenomena central to the functioning of the coral‐algal photosymbiosis. Such novel symbiotic biomaterials can be exploited for the engineering of synthetic microbial consortia and as a biomimetic model system for the coral‐algal symbiosis.